Medical negligence in Malaysia : cases and commentary - Jahn Kassim, Puteri Nemie (Sweet & Maxwell Asia, 2009)
As the frontiers of medical knowledge and technology are continually challenged, the performance of medical professionals and providers of medical care is increasingly put under scrutiny. Higher expectations are placed on the standard of treatment, skill and care provided by medical processionals. This has led to increasingly more medical negligence claims.